Use of magnetic resonance imaging to support dose selection in a phase II trial of baricitinib combined with conventional synthetic disease-modifying antirheumatic drugs in rheumatoid arthritis - Peterfy, C; Dicarlo, J; Emery, P; Genovese, MC; Keystone, EC; Taylor, PC; Schlichting, DE; Beattie, SD; Luchi, M; Macias, W (Journal of Rheumatology, 2019)
Objective Magnetic resonance imaging (MRI) was used in a Phase IIb study (NCT01185353) of baricitinib in patients with RA to support dose selection for the Phase III program. Methods 301 patients with active RA on stable methotrexate were randomized 2:1:1:1:1 to placebo or once-daily baricitinib (1-, 2-, 4-, or 8-mg) for up to 24 weeks. 154 patients with definitive radiographic erosion had MRI of the hand/wrist at baseline and weeks 12 and 24. Two expert radiologists, blinded to treatment and visit order, scored images for synovitis, osteitis, bone erosion, and cartilage loss. Combined inflammation (osteitis + 3x synovitis score) and total joint damage (erosion + 2.5x cartilage loss score) scores were calculated. Treatment groups were compared using analysis of covariance adjusting for baseline scores. Results Mean changes from baseline to week 12 for synovitis were -0.10, -1.50, and -1.60 for patients treated with placebo, baricitinib 4-mg, and baricitinib 8-mg, respectively (P=0.003 vs placebo for baricitinib 4- and 8-mg); mean changes for osteitis were 0.00, -3.20, and -2.10 (P=0.001 vs placebo for baricitinib 4-mg and P=0.037 for 8-mg) and mean changes for bone erosion were 0.90, 0.10, and 0.40 (P=0.089 for 4-mg and P=0.275 for 8 mg), respectively in these treatment groups. Conclusion Using MRI findings in this subgroup of patients suggest suppression of synovitis, osteitis, and combined inflammation by baricitinib 4- and 8-mg, which corroborate previously demonstrated clinical efficacy of baricitinib and increase confidence that baricitinib 4-mg could positively effect reduction of the radiographic progression in Phase III studies.